Methodological questions of the process structure benchmarking analyses planned in relation to the international Airport of debrecen - Palatinus, Brigitta (Acta Agraria Debreceniensis, 2014)
From June 2012 continuous traffic has begun between London Luton and Debrecen at the International Airport of Debrecen, which is considered a milestone in the growth of passenger traffic. The goal of this research is to demonstrate the fact that growt of passengers depends, on the visitors satisfaction with services used by them. The research of the customer service requires to develop process structure that includes the services used by the passengers from arriving at the airport to leaving the airport. A process structure like this allows us to carry out a benchmarking method to compare the passaenger services of other cities. To build up a structure we have to make segmentation according to the travellers’ motivation because they use different services according to their motivation. A questionnaire of customer satisfaction will be presented which results are the basis of the creation of benchmarking and creation of process structures.